Campus teaching: an effort to enchance the primary education quality in remote area - Hariyanti, Hariyanti; Cahya Permady, Gigieh; Irayanti, Irma; Alia Sari, Filma; Istianah, Anif; Retnasari, Lisa (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2023)
The purpose of this study was to describe the activities, roles, challenges, and opportunities of Batch 3 of the campus teaching program. This research was qualitative and employed descriptive methods. The study was conducted in SDN 08 Lubuk Dalam, Siak Regency, Riau. This study's informants were field supervisors and students of the campus teaching program, as well as the principal, teachers, and a number of students of SDN 08 Lubuk Dalam. Observation, in-depth interviews, and documentation research were employed to collect data. Moreover, source triangulation was utilized for the technical testing of data validity. According to the study's result, the activities and duties of the campus teaching program included literacy, numeracy, administration, and technology adaptation. These programs all contribute to improving student literacy and numeracy, learning motivation, and implementing the school's Minimum Competency Assessment. In addition, there are also challenges and opportunities in the campus teaching program at the school, including the location of the school, which is in a remote area. Access to the school is very challenging because it has to go through the oil palm plantation road; internet access at the school location and the non-existent electricity network are challenging, so school activities rely on generators. In contrast, the opportunities analyzed include the high tolerance at SDN 08 Lubuk Dalam among the diverse ethnicities, cultures, and religions that are strong in the school environment and the high teaching and learning spirit of the students and teachers amid challenges and limitations.This research contributes as evaluation material for schools.